2018
DOI: 10.1016/j.semarthrit.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis and risk of chronic obstructive pulmonary disease or asthma among women: A marginal structural model analysis in the Nurses’ Health Study

Abstract: In this prospective cohort study, RA was associated with increased risk for incident COPD, independent of lifestyle confounders and mediators after diagnosis, including smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
5
31
1
Order By: Relevance
“…However, the strength of association was attenuated after adjustment for newly considered confounders, and the relationship was not statistically significant in the incident RA cohort. Thus, the overall findings from this study reflect the uncertainty of existing literature, with some studies supporting an association between asthma and RA (4-8,29-31) and others refuting such an association (24,(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 63%
“…However, the strength of association was attenuated after adjustment for newly considered confounders, and the relationship was not statistically significant in the incident RA cohort. Thus, the overall findings from this study reflect the uncertainty of existing literature, with some studies supporting an association between asthma and RA (4-8,29-31) and others refuting such an association (24,(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, MAA adducts demonstrated marked colocalization with citrulline, CD19+ B cells, and type II collagen, most frequently observed in RA-ILD lung tissue. This study is among the first to characterize a biomarker for RA-ILD that has leveraged a comparator population incorporating RA patients with other chronic lung diseases that may be overrepresented in RA (33). Taken together, our findings suggest that MAA-modified proteins and resulting immune responses may serve as useful biomarkers for RA-ILD and that MAA-modified proteins may contribute to the pathogenesis of RA-ILD.…”
Section: Discussionmentioning
confidence: 69%
“…Prior studies have demonstrated a positive association between RA and subsequent risk of developing COPD . However, we identified only 2 studies examining COPD as an RA risk factor, neither of which were prospective.…”
Section: Discussionmentioning
confidence: 99%